Seabirds, fisheries, and cameras - (:unkn) unknown (My University, 2010)
Who will win the fight over scarce sardines in the Benguela ecoregion? In this upwelling system off southern Africa, once vast pelagic (open-ocean) fish stocks have decreased substantially as a result of inherent population variability, climate change, and fishing pressure (van der Lingen et al. 2006). Off the coast of Namibia, catches of sardines (Sardinops sagax) and anchovies (Engraulis encrasicolus) are now < 2% of those taken during the 1960s, and populations of endemic Cape cormorants (Phalacrocorax capensis), African penguins (Spheniscus demersus), and Cape gannets (Morus capensis), all of which depend on these pelagic fish, have declined to < 20% of levels recorded prior to industrial fishing (Crawford 2007). Off the coast of South Africa, sardine stocks declined from 4.2 million to 0.5 million metric tons (t) between 2002 and 2009, and pelagic fish showed substantial distribution shifts (Roy et al. 2007; Coetzee et al. 2008).
Keywords: African Research